2020
DOI: 10.1039/c9ob02098e
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic route to 1,4-disubstituted tetrahydro-β-carbolines and tetrahydropyranoindoles via ring-opening/Pictet–Spengler reaction of aziridines and epoxides with indoles/aldehydes

Abstract: A route to 1,4-disubstituted tetrahydro-β-carbolines and tetrahydropyrano[3,4-b]indoles in high yields and stereoselectivity via SN2-type ring opening/Pictet–Spengler reaction of aziridines and epoxides with indoles is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 98 publications
0
10
0
1
Order By: Relevance
“…Among the large number of THBCs, C1-substituted derivatives widely exist in nature as a constituent of indole alkaloids; consequently, there have been many reports on their syntheses including those involving modern transition-metal catalysts (Scheme ). Most of them adopted the well-known Pictet–Spengler (PS) reaction, which however proves less useful when 1-vinyl-substituted THBCs are targeted. Only a few reports exist where N -allyl, allenyl, or propargyl derivatives of tryptamine were exposed to rhodium, gold and palladium catalyst respectively (Scheme a–c), besides other methods , employing oxidative C­(sp 3 )–H olefination at the C1 position of the preformed THBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the large number of THBCs, C1-substituted derivatives widely exist in nature as a constituent of indole alkaloids; consequently, there have been many reports on their syntheses including those involving modern transition-metal catalysts (Scheme ). Most of them adopted the well-known Pictet–Spengler (PS) reaction, which however proves less useful when 1-vinyl-substituted THBCs are targeted. Only a few reports exist where N -allyl, allenyl, or propargyl derivatives of tryptamine were exposed to rhodium, gold and palladium catalyst respectively (Scheme a–c), besides other methods , employing oxidative C­(sp 3 )–H olefination at the C1 position of the preformed THBCs.…”
Section: Introductionmentioning
confidence: 99%
“…In the third step, compound 12a was reacted with benzaldehyde for the PS cyclization. Most commonly, ptoluenesulphonic acid (p-TSA) is used as a catalyst for this reaction [40,41]. So initially, p-TSA in toluene as a solvent under reflux condition was used.…”
Section: Resultsmentioning
confidence: 99%
“…89 This alternative method involved a cascade process of Groebke-Blackburn-Bienaymé reaction to form the fused adduct, acid-catalyzed Pictet-Spengler cyclization to obtain dihydropyridine, and oxidation by atmospheric O 2 to finally afford a series of In 2020, Wani and coworkers reported that the 1,4disubstituted tetrahydro-β-carbolines and tetrahydropyrano [3,4-b]indoles 105 could be obtained in high yields and stereoselectivity by a simple and efficient method using indoles 102, aziridines or epoxides 103, and benzaldehydes 104 (►Scheme 25). 91 In this report, LiClO 4 -catalyzed ring opening of aziridines and epoxides with indoles was performed in acetonitrile at 85°C for 3 hours, followed by ptoluenesulfonic acid-catalyzed Pictet-Spengler cyclization with benzaldehydes. To improve the efficiency of the Pictet-Spengler cyclization, various reaction parameters were screened.…”
Section: Three-component Pictet-spengler Cyclization-based Domino Rea...mentioning
confidence: 99%